IDENTIFICATION OF SIDE EFFECTS OF USE OF ANTI TUBERCULOSIS DRUGS IN PADANG SERAI AND TELAGA DEWA HEALTH CENTERS BENGKULU CITY 2024 - Khasanah, Heti Rais; Pudiarifanti, Nadia; Baharyati, Delta; Meliyarta, Elda; Nurul Inayah, Azizah (Avicenna: Jurnal Ilmiah, 2024)
Background: Tuberculosis is an infectious disease caused by Mycobacterium Tuberculosis, which can attack the lungs and other organs. Despite the progress that has been achieved, the number of tuberculosis cases is one of the biggest challenges faced and requires attention from all parties. Method: This study is a prospective observational study. The population in this study was 37 patients at the Telaga Dewa and Padang Serai Health Centers, Bengkulu City. The sampling technique was total sampling with inclusion criteria for patients seeking treatment at the Telaga Dewa and Padang Serai Health Centers, Bengkulu City. Results: The side effects of anti-tuberculosis drugs that occurred at the UPTD of the Padang Serai and Telaga Dewa Community Health Centers were red urine 100%, lack of appetite and nausea, vomiting 51.35%, weakness and pain 37.83%, stomach ache 32.43% , itching 29.72%, tingling and shortness of breath 16.21%, skin and eye color 13.51%, hearing loss 8.10%, visual disturbances, seizures and unconsciousness 2.7%. Conclusion; The majority of TB sufferers are male. The most frequent side effects of anti-tuberculosis drugs are red urine, lack of appetite, nausea, vomiting, pain. Keywords : Side effects; OAT; tuberculosis,